ASSOCIATION OF GLYCAEMIC CONTROL WITH PREMATURE EJACULATION AMONG TYPE 2 DIABETES MELLITUS PATIENTS ATTENDING IN A TERTIARY CARE HOSPITAL OF BANGLADESH - Ahmed, Md. Ashraf Uddin; Morshed, ASM; Yasmin, Farzana (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Premature ejaculation is three times higher in diabetic population and its onset is 10 to 15 years earlier than persons without diabetes. The aim of this study was to find out the association of glycaemic control with premature ejaculation among patients with Type 2 DM attending in a tertiary care hospital of Bangladesh. METHODOLOGY This descriptive cross-sectional study was conducted in the outpatient department of BIRDEM general hospital from July 2017 to June 2018. A total of 225 adult patients with type 2 DM were recruited and diagnosis was confirmed as per ADA 2016 criteria. A face to face interview was conducted using premature ejaculation diagnostic tool (PEDT). RESULTS Mean age of patients having PE was 38.36±8.89 and age group of 60–69 years had higher incidence rate. Most of the respondents were married (73.3%). Among the study population, the prevalence of PE was 55.6%. The analysis also showed that duration of diabetes was associated with the increasing risk of PE. Almost half of PE patients (48%) were suffering from type 2 DM for more than 10 years. PE was significantly higher (p<0.001) among patients with poor glycaemic control (HbA1c >7). CONCLUSION The results provide evidence that PE is a highly prevalent sexual dysfunction among type 2 DM patients in Bangladesh. Moreover, PE largely remains underdiagnosed and untreated. The health system needs to develop appropriate strategies including early diagnosis, awareness, and health education programs for appropriate treatment.